2020
DOI: 10.1038/s41598-020-59314-7
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin controls microbiota in colitis by goblet cell differentiation and antimicrobial peptide production through Toll-like receptor 4 signalling

Abstract: Microbial dysbiosis has long been postulated to be associated with the pathogenesis of inflammatory bowel disease (IBD). Although evidence supporting the anti-colitic effects of melatonin have been accumulating, it is not clear how melatonin affects the microbiota. Herein, we investigated the effects of melatonin on the microbiome in colitis and identified involvement of Toll-like receptor (TLR) 4 signalling in the effects. Melatonin improved dextran sulfate sodium (DSS)-induced colitis and reverted microbial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 61 publications
(81 reference statements)
1
46
1
4
Order By: Relevance
“…The fact that MLT enhanced the relative abundance of phyla Bacteroidetes and decreased Proteobacteria phyla was similar to the studies of Kim et al ( 15 ) and Yin et al ( 44 ) in mice. Thus, we speculate that a variety of crucial metabolic pathways within ruminal microbiota were likely to be regulated by MLT treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The fact that MLT enhanced the relative abundance of phyla Bacteroidetes and decreased Proteobacteria phyla was similar to the studies of Kim et al ( 15 ) and Yin et al ( 44 ) in mice. Thus, we speculate that a variety of crucial metabolic pathways within ruminal microbiota were likely to be regulated by MLT treatment.…”
Section: Discussionsupporting
confidence: 89%
“…The MLT is one of the most-essential hormones involved in regulating circadian rhythms in the host, and the complex effects of this hormone on the gut microbiome has just begun to be studied ( 15 ). For instance, Ma et al ( 16 ) demonstrated a firm connection among MLT, gut microbiota and mucosal immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid eye-movement sleep-behavior disorder patients are managed by a combination treatment of melatonin and clonazepam [ [17] , [18] , [19] ]. The sensing of bacteria through Toll-like receptor-4, and regulation of bacteria through altered goblet cells and antimicrobial peptides, are all involved in the anticolitic effects of melatonin in inflammatory bowel disease [ 20 ]. Melatonin is involved in the aging process, growth towards puberty, and modulation of blood pressure [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Akkermansia muciniphila)的丰度,从而缓解 IL-10 敲除小鼠的自发性结肠炎 [39] 。 Nlrp6 −/− 小鼠肠道菌群的异常还通过诱导肠上皮细胞中的 IL-6 信号促进结肠炎到 结肠癌的转变 [40] 。然而,也有学者发现 NLRP6 炎症小体在他们的实验中并不改 变肠道菌群 [41,42] ,提示对于复杂的实验系统,研究对照的设置非常重要,遗传、 环境等影响肠道菌群的因素都应该考虑进来,否则可能会得出片面的结论 [43] 。 NLRP1 炎症小体也参与对肠道菌群的调控。有研究发现,NLRP1 敲除小鼠 的肠炎和肠癌都比野生型对照严重, 而同笼饲养以后野生型小鼠的疾病表型明显 加重,说明在 NLRP1 敲除的情况下,促炎的肠道菌可以转移给野生型小鼠而致 病 [44] 。因此,NLRP1 与肠道菌群(特别是激活 NLRP1 炎症小体的特定菌种)的相 互作用,以及 NLRP1 与其他免疫基因在维持肠道稳态方面可能存在重叠/互补关 系,其中的机制有待进一步深入研究。 还有研究发现肠道嗜酸性粒细胞通过 IL-1β 调节肠道 IgA 的产生,从而维持 肠道菌群的稳态 [45] 。而上文中也提及,AIM2 和 NLRP6 炎症小体对肠道菌群的 塑造主要是通过 IL-18 实现的, IL-18 本身的缺失也导致菌群紊乱和肠炎易感 [30,35,36] 。 A c c e p t e d https://engine.scichina.com/doi/10.1360/SSV-2021-0282 [46] 。 虽然有研究报道显示 NOD1 和 NOD2 都不会影响小鼠正常肠道微生物群系的组 成和结构 [47] ,但也有研究认为 NOD1 或 NOD2 基因的缺陷都会引起肠道共生菌 群的变化 [46] 。在高脂饲料饲养的条件下,NOD1 缺失小鼠肠道菌群的改变与野生 型对照鼠有明显差异,其炎症指标也有显著升高,这些因素使得该品系的小鼠更 早发展出糖尿病 [48] 。由于 NOD2 是重要的炎症性肠病易感基因 [49][50][51] ,而炎症性 肠病的发生发展与菌群紊乱密切相关,因此更多的研究认为 NOD2 对于肠道菌 群的塑造是有影响的。有研究发现 NOD2 敲除导致肠道菌群失调,但这种失调 并没有导致粘膜组织异常或免疫平衡改变 [52] 。而其他研究则显示,NOD2 缺失小 鼠在拟杆菌属(Bacteroides)方面与野生型小鼠明显不同,也更容易发生结肠炎和 肠癌 [53,54] 。另外,携带 NOD2 功能缺失变体的乳糜泻患者表现出肠道微生物群 系的改变 [55] ,结肠袋炎患者的"有益"细菌粪杆菌属普拉梭菌、拟杆菌、疣微 菌科(Faecalibacterium prausnitzii, Bacteroides, Ruminococcaceae)水平降低 [56] 。这 些彼此差异的结果再次表明 [46] ,宿主遗传因素和环境因素对肠道菌群的塑造都 有重要影响,在没有条件把所有的来龙去脉都研究清楚的情况下,严格的对照设 置对于实验结论最为重要。 3,TLR 对肠道菌群的影响 TLR 信号参与维持肠道稳态,或在特定条件下介导与菌群失调相关的肠道炎 症。IL-10 敲除小鼠在 SPF 条件下会自发结肠炎 [57] ;有趣的是,IL-10 缺陷小鼠 回交到 Myd88 -/-小鼠就不会自动发生结肠炎, 提示 TLR 信号参与肠道微生态失调 介导的炎症 [58] 。TLR 信号异常可干扰病原菌清除,导致微生态失调。对无菌的 Tlr5 -/-小鼠用有鞭毛或无鞭毛的侵袭性大肠杆菌定植后,继续在普通环境下饲养, 有鞭毛的大肠杆菌定植的 Tlr5 -/-小鼠出现结肠炎,而无鞭毛组没有发病,说明 TLR5 对细菌鞭毛蛋白的识别对维持肠道稳态非常重要 [59] 。耶尔森菌感染后存活 下来的 Tlr1 -/-小鼠肠道微生物群系失调,特征是δ-变形杆菌显著增多,该菌利用 耶尔森菌的四硫酸化呼吸途径旺盛扩增,快速超过其他细菌的丰度;移植这种失 A c c e p t e d https://engine.scichina.com/doi/10.1360/SSV-2021-0282 调的肠道菌能够使受体野生型小鼠更容易发生 DSS 诱导的结肠炎 [60] 。还有研究 发现,肠上皮细胞中 TLR4 过度激活不仅引起肠道菌群紊乱,而且增加了对肠炎 的易感性,并且这种症状可以传递给同笼饲养的野生型小鼠 [61] 。褪黑素可以改 善 DSS 诱导的结肠炎并逆转野生型小鼠的肠道菌群紊乱,但在 TLR4 敲除小鼠 中没有效果,原因是褪黑素通过 TLR4 信号显著增加杯状细胞、Reg3β 和厚壁菌 与拟杆菌的比例 [62] 。TLR2/MDR1A 双缺陷小鼠会发生暴发性结肠炎,CD11b + 髓 系细胞扩增,固有层 Th1 免疫反应增强,而这些表型与共生菌群密切...…”
Section: 白蚁孢子杆菌(Sporobacter Termiditis)和双裂副杆菌(parabacteroides Distasonis)则unclassified